Experimental study on the thixotropic strength of the marine soft clay from the Yangtze River estuary - Wang, Binghui; Huang, Yanyu; Zhu, Enci; Xiao, Xing; Wu, Qi (Frontiers in Marine Science, 2024)
Soft clay in the offshore area of the Yangtze River estuary has been investigated considering its basic physical properties. Forty-five unconfined compressive strength tests were conducted on the remolded marine soft clay to investigate the impacts of curing time T, water content w, plasticity index I P , and clay particle content ρ c on the thixotropic static shear strength ratio A s of the marine soft clay from the Yangtze River estuary. Results show that the stressstrain curves were primarily strain hardening and strain softening curve types. Unconfined compressive strength q u increased with an increase in T. All specimens with different basic physical properties were capable of thixotropic strength recovery. When T = 0-28 days, A s increased rapidly, while for T > 28 days, A s of most specimens increased slightly or tended to stabilize. The impacts of w, I P and ρ c on A s do not follow a consistent pattern, but there is a strong correlation between A s and w/w L (w L is the liquid-limit water content). For w/w L < 0.75, A s increased with increasing w/w L , whereas for w/w L ≥0.75, A s decreased with increasing w/w L . We proposed a simple and widely applicable power function prediction model for the As of the soft clay from the Yangtze River estuary.